HUKUM PERLINDUNGAN KONSUMEN TERHADAP SERVICE LAPTOP TIDAK PROFESIONAL DALAM PERSPEKTIF WAHBAH AZ-ZIHAILI (Studi Kasus Toko Service Laptop di Desa Pertumbukan Kecamatan Wampu Kabupaten Langkat - Hastati Isna Efelia; Zulham Zulham; Annisa Sativa (Fakultas Syari'ah dan Hukum UIN Sumatera Utara, 2019)
The problem in this study is the law of consumer protection for unprofessional laptop service whether it is protected or not. This research was conducted at the Laptop Service Shop in the Village of Growth in the District of Wampu Langkat Regency. This research is a field research namely research conducted at the location which is the object of research, namely in the Village of the District of Wampu Langkat District and library research. In this study the method used was interview and data obtained from the field. The conclusion of this thesis is the Consumer Protection Law Against unprofessional laptop services in the Wahbah Az-Zuhaili Perspective is mandatory, and the one who is obliged to provide responsibility is the Shop Owner who is the guarantor. Because according to Wahbah Az-Zuhaili's perspective, if something guaranteed is in the form of al-inAin (goods, not debt), the guarantor is demanded to surrender the guaranteed al-inAin, if indeed the goods still exist. But if it has been damaged, then he surrenders instead with similar items or at a value. Article 19 paragraph (1) of Law Number 8 of 1999 concerning consumer protection clearly stipulates: